Implementasi Extreme Programming Pada Perancangan Sistem Informasi Penjualan Buku Menggunakan Java - Lestari, Ade Fitria (JAIS - Journal of Accounting Information System, 2023)
Technology is needed by humans to facilitate all activities carried out so that they are fast and practical, besides that technology is used as a solution to problems in conventional systems. Conventional sales activities experience several problems such as recording activities, insecure archiving, manual calculations and loss of transaction data. From these problems, the purpose of this study is to design a sales information system, namely object-based book sales transactions in order to minimize errors and produce the information needed by users effectively and efficiently. The method used is Extreme Programming which is very suitable for developing and building object-oriented applications. This method has stages in the method including planning carried out problem finding and needs analysis, the design consists of system design with UML (Unified Modeling Language) and ERD (Entity Relationship Diagram) database design, coding in the form of application menu displays, testing with blackbox testing and software increase. The design of an OOP-based book sales information system using the Extreme Programming method is expected to help and facilitate users in managing data, sales transactions and reports.